The genetic risk factors for cerebral venous thrombosis: a case-control study in a Chinese national comprehensive hospital - Wang, Shaoying; Yao, Ming; Yang, Xinzhuang; Zhu, Yicheng; Peng, Bin (Thrombosis journal, 2024)
About 13-25% of cerebral venous thrombosis (CVT) cases lack clear etiology, which may be associated with underlying genetic factors. This study aims to investigate genetic factors in CVT patients using whole exome sequencing (WES). Thirty-eight CVT patients hospitalized underwent WES. 977 subjects with WES data from a community cohort study --the Shunyi cohort were as the control group. Using bioinformatics analysis, differential genes with rare damaging variants between two groups were filtered (P < 0.05). KEGG enrichment analysis was performed on the screened genes to identify pathways associated with CVT. Through analysis of medical history, routine tests, and imaging examinations, the etiology of 38 patients: 8 cases of antiphospholipid syndrome, 6 cases with hematologic diseases, 3 cases of protein C deficiency, and 2 cases of protein S deficiency. Five cases occurred during pregnancy or puerperium, and 3 cases had a history of oral contraceptive use, and so on. The etiology was unknown in 12 cases (31.6%), and the etiology of 4 patients were further clarified through WES: F9 c.838 + 1_838 + 16del, Hemizygote: F9 EX1-EX7 Dup; CBS c.430G > A, CBS c.949 A > G; F2 c.1787G > A; SERPINC1 c.409-11G > T. Comparing the WES data of two groups, a total of 179 different genes with rare damaging variants were screened (P < 0.05), with 5 genes of interest (JAK2, C3, PROC, PROZ, SERPIND1). Enrichment analysis of the 179 different genes revealed the complement and coagulation pathway and the mitogen activated protein kinases (MAPK) pathway were associated with CVT. For CVT patients with unknown etiology, WES could help identify the cause of CVT early, which is of great significance for treatment decisions and prognosis. In addition to the complement and coagulation pathway, MAPK pathway is associated with CVT, potentially related to platelet regulation and inflammatory response.